XEN‐augmented Baerveldt surgical success rate and comparison with the Ahmed Valve - Jorge Teixeira, Filipa; Sousa, David Cordeiro; Machado, Nuno Martins; Caiado, Filipa; Correia Barão, Rafael; Sens, Paula; Abegão Pinto, Luis (Acta ophthalmologica (Oxford, England), 2020)
© 2020 Acta Ophthalmologica Scandinavica Foundation. Published by John Wiley & Sons Ltd. Purpose: The Baerveldt-XEN technique is intended to reduce the risk of early hypotony after Baerveldt implant, while keeping a good long-term intra-ocular pressure (IOP) control. The aim of this study is to discuss the surgical success rate of the Baerveldt-XEN and compare it with the commercially available flow-restrictor device (Ahmed glaucoma valve - AGV). Methods: Single-centre, cohort study. Consecutive glaucoma patients with uncontrolled IOP > 21 mmHg on maximum tolerated medical therapy, and who had an aqueous shunt as the planned surgical procedure. Patients underwent implantation of Baerveldt-XEN. An age-, gender- and glaucoma aetiology-matched database of AGV patients was used for comparison. Complete surgical success was defined as a final IOP between 6 and 21 mmHg, and 20% reduction from baseline with no need for IOP-lowering medication. Qualified success was the same criteria but resorting to medications. Results: Twenty-four eyes from 24 subjects with glaucoma were included in this study, 12 patients underwent Baerveldt-XEN implantation and 12 AGV. Twelve months after the Baerveldt-XEN implant, the IOP reduced from 33 ± 9 mmHg to 14 ± 3 mmHg (p < 0.001). The qualified and complete success rate was 50% and 25%, respectively. With the AGV, the IOP reduced from 29 ± 7 mmHg to 16 ± 7 mmHg (p = 0.001). The matched AGV group compared to the Baerveldt-XEN, presented a higher complete success rate (58.3%) and a qualified success rate of 33.3% (p = 0.72). No sight-threatening complications were recorded in both groups. Conclusions: The Baerveldt-XEN disclosed a low complete success rate at 1 year of follow-up, although with no major safety concerns. While studies with a longer follow-up are needed to demonstrate the potential advantages and disadvantages of the Baerveldt-XEN, this technique may be less likely to achieve drop-free efficacy when compared to other flow-restrictor strategies.